2018
DOI: 10.2478/vzoo-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

New Records on Acanthocephalans from California Sea Lions Zalophus californianus (Pinnipedia, Otariidae) from California, USA

Abstract: To increase the currently limited knowledge addressing acanthocephalans parasitizing California sea lions (Zalophus californianus), 33 animals including pups, juvenile and adult males and females from the Marine Mammal Center (TMMC), Sausalito, California, USA were examined. Totally, 2,268 specimens of acanthocephalans representing five species from the genera Andracantha (A. phalacrocoracis and Andracantha sp.), Corynosoma (C. strumosum and C. obtuscens) and Profilicollis (P. altmani) were found. Profilicolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…We added measurements of cement glands, bursa, neck, and three hooks (apical, middle and posterior), female reproductive system, and the number of genital spines, to our description. An account of our smaller subset of 10 males and 12 females from the same California collection was briefly outlined by Lisitsyna et al (2018) and the fewer measurements provided there were similar to those reported by Lisitsyna et al (2019). Smales (1986) redescribed C. australe from Neophoca cinerea (type host) and Arctocephalus pusillatus in South Australia with measurements comparable to but at variance with measurements of our California material from Zalophus californianus.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 55%
See 2 more Smart Citations
“…We added measurements of cement glands, bursa, neck, and three hooks (apical, middle and posterior), female reproductive system, and the number of genital spines, to our description. An account of our smaller subset of 10 males and 12 females from the same California collection was briefly outlined by Lisitsyna et al (2018) and the fewer measurements provided there were similar to those reported by Lisitsyna et al (2019). Smales (1986) redescribed C. australe from Neophoca cinerea (type host) and Arctocephalus pusillatus in South Australia with measurements comparable to but at variance with measurements of our California material from Zalophus californianus.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 55%
“…Of the 1,201 specimens originally collected from the single sea lion in California in 2015, 51 specimens (24 males, 27 females) were initially reported as C. obtuscens (Lisitsyna et al, 2018; Figs. 1, 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017), and Lisitsyna et al . (2018). None of these works, however, addressed the impact of long isolation on morphometric variability.…”
Section: Discussionmentioning
confidence: 99%
“…Sea lions inhabit mainly beaches, rocks, islets and islands [29] estimated 30,000 California sea lions inside the Gulf of California. This species is one of the most abundant and recognized pinniped species from British Columbia, Canada to Baja California, Mexico [32,33].…”
Section: California Sea Lion (Zalophus Californianus Lesson 1828)mentioning
confidence: 99%